Taiwan: democratic David in 21st century east Asia - Chin, John J.; Rector, Staten (Frontiers in Political Science, 2025)
Taiwan is not just a victim-in-waiting, damsel in distress, or pawn in a new Cold War. Taiwan stands as an exemplar: the world’s first “Chinese democracy” and a democratic David in the shadow of an autocratic Goliath. Taiwan’s success in deepening democracy and resisting Chinese sharp power may hold lessons on how to counter the rising global tide of authoritarianism. To elucidate these lessons, we review Taiwan’s democratic history and ongoing efforts to defend its hard-won democracy.